Ecología trófica del jurel Trachurus murphyien el Perú entre 1977 – 2011 - Alegre, Ana (2013)
We analyzed the spatiotemporal variability of Jack mackerel Trachurus murphyi diet off Peru from 1977 to 2011. A total of 21058 stomachs were analyzed using bivariate methods and the Multivariate Regression Tree Model (MRT). The gravimetric composition of the diet was used as response variable with respect to different predictor variables such as years, depth of the 15°C isotherm, Southern Oscillation Index (SOI), Index of the Pacific Decadal Oscillation (PDO), sea surface temperature anomaly, zone (north, center and south) and distance to the coast. Our results allowed us to identify two different scenarios. From 1977 to 2000 the Jack mackerel T. murphy diet was strongly dominated by Euphausiidae, and since 2000 when T. murphyi consumed a greater diversity of prey, mainly Euphausiidae, squat lobster Pleuroncodes monodon and Zoea. It is noted that the first scenario corresponds to warm conditions and the second to cold conditions, both coincident with observed multidecadal periods. In contrast to previous studies showing that the anchovy Engraulis ringens is an abundant prey, in this study anchovy was not significantly important. Spatially, the Euphausiidae dominated the diet in central-northernPeru, while further south the prey composition was more diverse. The diet also varied significantly according to the distance from the coast (higher proportion of P. monodoncloser to the coast) and the ontogenic stages.